Common Bile Duct Exploration in an Elderly Asian Population - Shelat, Vishal G. (Int Surg, 2015)
Common bile duct exploration (CBDE) is an accepted treatment for choledocholithiasis. This procedure is not well studied in the elderly population. Here we evaluate the results of CBDE in elderly patients (>70 years) and compare the open (group A) with the laparoscopic group (group B). A retrospective review was performed of elderly patients with proven common bile duct (CBD) stones who underwent CBDE from January 2005 to December 2009. There were 55 patients in group A and 33 patients in group B. Mean age was 77.6 years (70–91 years). Both groups had similar demographics, liver function tests, and stone size—12 mm (range, 5–28 mm). Patients who had empyema (n = 9), acute cholecystitis (n = 15), and those who had had emergency surgery (n = 28) were more likely to be in group A (P < 0.05). The mean length of stay for group A was 11.7 ± 7.3 days; for group B, 5.2 ± 6.3 days; the complication rate was higher in group A (group A, 38.2%; group B, 8.5%; P = 0.072). The overall complication and mortality rate was 29.5% and 3.4%, respectively. CBDE can be performed safely in the elderly with accepted morbidity and mortality. The laparoscopic approach is feasible and safe in elective setting even in the elderly.